2016
DOI: 10.1002/cncy.21749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Afirma gene expression classifier on cytopathology diagnosis and rate of thyroidectomy

Abstract: BACKGROUND The Afirma gene expression classifier (GEC) assesses malignancy risk in patients with indeterminate thyroid nodules. Afirma putatively reduces costs by classifying certain nodules as benign and thereby avoiding unnecessary surgery. Prior studies have evaluated its impact exclusively on GEC‐tested nodules. The objective of the current study was to analyze the effect of Afirma on 1) cytopathology diagnosis, 2) the rate of surgery, and 3) the rate of malignancy on all indeterminate nodules at a high‐vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 18 publications
5
52
0
Order By: Relevance
“…Findings in several of the studies designed to assess the contribution of AGEC to risk stratification in thyroid nodules with indeterminate cytology have actually led the authors of these same studies to question and, in some cases, actually doubt the benefits of AGEC testing to risk of malignancy stratification and/or to patient care. In a study from one of our institutions (CSMC), Sacks et al reported a significant increase in the incidence of indeterminate FNA diagnoses and a significant decrease in the incidence of benign FNA diagnoses after molecular testing became routinely available, leading the authors to suggest that Afirma may shift FNA interpretation toward Bethesda III/IV while not significantly altering the institutional rates of thyroid surgery and thyroid malignancy . In another study by Roychoudhury et al the rate of Afirma was 1.5 times higher than the rate of cytology in classifying nodules that were subsequently diagnosed as nodular goiter as “suspicious.” In that study, among FNAs interpreted as suspicious for malignancy (Bethesda V), cytology performed better than AGEC in correctly predicting malignancy while in nodules interpreted as AUS (Bethesda III) the rates of malignancy for cytology and AGEC‐SUSP were similar, leading the authors to conclude that AGEC did not further contribute to patient management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings in several of the studies designed to assess the contribution of AGEC to risk stratification in thyroid nodules with indeterminate cytology have actually led the authors of these same studies to question and, in some cases, actually doubt the benefits of AGEC testing to risk of malignancy stratification and/or to patient care. In a study from one of our institutions (CSMC), Sacks et al reported a significant increase in the incidence of indeterminate FNA diagnoses and a significant decrease in the incidence of benign FNA diagnoses after molecular testing became routinely available, leading the authors to suggest that Afirma may shift FNA interpretation toward Bethesda III/IV while not significantly altering the institutional rates of thyroid surgery and thyroid malignancy . In another study by Roychoudhury et al the rate of Afirma was 1.5 times higher than the rate of cytology in classifying nodules that were subsequently diagnosed as nodular goiter as “suspicious.” In that study, among FNAs interpreted as suspicious for malignancy (Bethesda V), cytology performed better than AGEC in correctly predicting malignancy while in nodules interpreted as AUS (Bethesda III) the rates of malignancy for cytology and AGEC‐SUSP were similar, leading the authors to conclude that AGEC did not further contribute to patient management.…”
Section: Discussionmentioning
confidence: 99%
“…The Afirma Gene Expression Classifier (AGEC) (Veracyte Inc, South San Francisco, CA), currently the most frequently utilized such test, is a proprietary 142 mRNA‐based assay that was developed to categorize cytologically indeterminate thyroid nodules as benign with high sensitivity and high negative predictive value (NPV) . However, variable NPVs across institutions (NPVs from 75% to 95%), high rates of AGEC‐suspicious (AGEC‐SUSP) results in indeterminate nodules that exhibit Hürthle cell change on FNA and are benign at resection and AGEC‐SUSP results in indeterminate nodules diagnosed as NIFTP on histological evaluation underscore the need to improve molecular‐based triaging of cytologically indeterminate thyroid nodules . RosettaGX ® Reveal™ (Reveal) (Rosetta Genomics Philadelphia, PA) is a more recently developed test that utilizes RNA extracted from Papanicolaou or Romanowsky‐type (Diff‐Quik and Giemsa) stained direct or ThinPrep smears and algorithms based on a panel of 24 microRNAs to classify cytologically indeterminate thyroid nodules into benign, suspicious for malignancy or positive for medullary carcinoma .…”
Section: Introductionmentioning
confidence: 99%
“…But the positive predictive value (PPV) of the GEC was lower than expectation according to an independent study from the United States . Additionally, Afirma may cause unintended effects, leading to increasing number of indeterminate fine‐needle aspirations but not effecting thyroidectomy rate and malignancy yield of TC . Meanwhile, it is worth noting that GEC needs signals from above 100 genes to improve accuracy .…”
Section: Discussionmentioning
confidence: 95%
“…Cytomolecular testing of thyroid nodules has the potential to distinguish indeterminate as either benign or neoplastic (including both premalignant and malignant pathology) and thus to improve the quality of care and guide surgical decision making. However, the incorporation of molecular testing into the options for diagnosis in thyroid cancer may actually contribute to changes in cytopathology interpretation and changes in the rates of indeterminate nodules . Even final histologic assessment of benign versus malignant disease is in transition, as indicated by the recent change in the nomenclature when discussing noninvasive, encapsulated follicular variant of PTC, which was recently changed to be considered nonmalignant and redefined as a noninvasive follicular tumor with papillary‐like features (NIFTP).…”
Section: Limitations Of Thyroid Cytologic and Histopathologic Evaluationmentioning
confidence: 99%
“…Designed to lower patient morbidity and the cost of care by decreasing unnecessary surgery for benign thyroid nodules, the majority of studies have demonstrated the utility of the Afirma GEC, whereas others have questioned the actual cost‐benefit analysis of reflexively incorporating it into clinical care . Behind some of the various interpretations of the performance of the GEC are the inherent differences in agreement among thyroid cytopathologists .…”
Section: The Development Of Thyroid Molecular Testingmentioning
confidence: 99%